Pleomorphic Adenoma with Sarcomatous Change in a Lacrimal Gland - Sung, Kyoung-Su (J Korean Neurosurg Soc, 2015)
A 69-year-old man was referred with left exophthalmos. Computed tomographic (CT) findings detected a well-circumscribed mass in the left side of the intraorbital cavity. At that time, he refused the further evaluation and treatment. About three years later, the size of the mass had enlarged, and the patient's symptoms were getting worse. The mass was completely removed with frontotemporal craniotomy and superolateral orbitotomy. In operative findings, the mass had originated in the lacrimal gland and was well-encapsulated without invasion to the surrounding tissue. In the pathologic findings, the tumor consisted of pleomorphic adenoma with osteosarcomatous change of stromal components. Postoperatively, the adjuvant radiotherapy was done four weeks later. The patient's symptoms were improved. The pleomorphic adenoma with osteosarcomatous change is extremely rare and appropriate treatment is not clearly established. We would like to report this rare case with a review of the literature.